Navy, Air Force Will Wrap Up Nuclear Commonality Analysis In July - Hudson, Lee (Inside the Pentagon's Inside Missile Defense, 2014)
Each working group is composed of subject-matter experts on the Navy Trident II D5 and Air Force Minuteman III strategic weapon systems, Navy spokeswoman April Crew-Kelly wrote in a June email.